2011
DOI: 10.1017/s003329171100242x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal anterior cingulate cortical activity during emotional n-back task performance distinguishes bipolar from unipolar depressed females

Abstract: Background Depression in the context of bipolar disorder (BDd) is often misdiagnosed as unipolar disorder depression (UDd) leading to poor clinical outcomes for many bipolar sufferers. We examined neural circuitry supporting emotion regulation in females with either BDd or UDd as a first stage toward identifying biomarkers that may differentiate BDd from UDd. Method Fifty-seven females aged 18–45 years participated in this study: 23 with UDd, 18 with bipolar disorder type I depression (BDId) and 16 healthy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 49 publications
8
98
1
Order By: Relevance
“…An fMRI study of bipolar I depression explored blood oxygenation level-dependent (BOLD) response during a 2-back working memory task and found that medicated depressed subjects with bipolar I disorder exhibited increased left DLPFC activation compared with healthy subjects (Deckersbach et al 2008). An increased activation pattern has also been found in studies in predominantly medicated unipolar depressed subjects (Fitzgerald et al 2008; Bertocci et al 2012) in which performance on n-back tasks is associated with increased anterior cingulate response, which could represent compensatory activation. However, Townsend et al (2010), found that, relative to healthy comparison subjects, medicated subjects with bipolar I depression exhibited decreased activation in the right DLPFC and the posterior parietal cortex [Brodmann area (BA) 40] during a working memory task.…”
Section: Introductionmentioning
confidence: 62%
“…An fMRI study of bipolar I depression explored blood oxygenation level-dependent (BOLD) response during a 2-back working memory task and found that medicated depressed subjects with bipolar I disorder exhibited increased left DLPFC activation compared with healthy subjects (Deckersbach et al 2008). An increased activation pattern has also been found in studies in predominantly medicated unipolar depressed subjects (Fitzgerald et al 2008; Bertocci et al 2012) in which performance on n-back tasks is associated with increased anterior cingulate response, which could represent compensatory activation. However, Townsend et al (2010), found that, relative to healthy comparison subjects, medicated subjects with bipolar I depression exhibited decreased activation in the right DLPFC and the posterior parietal cortex [Brodmann area (BA) 40] during a working memory task.…”
Section: Introductionmentioning
confidence: 62%
“…In a previous study (15), we applied an emotional go/no-go task, which yielded behavioral distraction effects in the emotional compared with the neutral condition, but no behavioral alterations in bipolar disorder, although activation was increased in frontal and limbic regions. Similar activation increases without behavioral effects were found in working memory tasks with sad mood induction (16) and face distractor stimuli (17). Critically, these studies could not clarify whether the observed hyperactivations reflect altered processing of the cognitive tasks (e.g., as a compensatory effect) or simply aberrant emotional processing.…”
Section: Discussionmentioning
confidence: 83%
“…A meta-analysis [11] found that MDD showed overreactive salience network (amygdala, dorsal anterior cingulate cortex, and insula) and low response of dorsolateral prefrontal cortex and dorsal striatum to negative information. In addition, different brain activation patterns have been observed by directly comparing activations BD and MDD during performing a series of tasks (e.g., executive function [12,13], facial expressions [1416], and reward [17]). However, the findings of these studies vary from the tasks performed by participants, posing a challenge to compare data obtained from different cognitive studies.…”
Section: Introductionmentioning
confidence: 99%